PENGARUH LITERASI KEUANGAN DAN PENGGUNAAN FINTECH TERHADAP PERILAKU KEUANGAN MAHASISWA DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Warda, Widya; Arsal, Muryani; Nur Abdi, Muhammad (STKIP Subang, 2026)
This study aims to analyze the influence of financial literacy and the use of financial technology (fintech) on students' financial behavior at Muhammadiyah University of Makassar. This research applies a quantitative approach with an explanatory causal design. The sample was selected using purposive sampling, involving 110 respondents who are active students and fintech users. Data were collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that: (1) financial literacy has a positive and significant effect on students' financial behavior; and (2) the use of fintech also has a positive and significant effect on students' financial behavior. These findings indicate that a higher level of financial understanding and appropriate use of fintech can improve students' ability to manage their finances in a more effective, planned and responsible manner.